Bifurcation lesions in the context of a PCI CTO – insight from a Belgrade single-center CTO registry - Juričić, Stefan; Tešić, Milorad; Dobrić, Milan; Stojković, Siniša (Vojnosanitetski pregled, 2023)
Background/Aim. Chronic total occlusions (CTOs) of the coronary artery are still one of the most complex procedures in the treatment of coronary arteries. If there is a bifurcation lesion within the CTO, it is certainly one of the biggest challenges for interventional cardiologists. Methods. We present a retrospective analysis of patients from our center who underwent percutaneous coronary intervention (PCI) with a bifurcation lesion within the CTO and a side branch with a diameter of 2 mm or more from January 2017 to December 2020. Results. Out of the total 216 patients in the four-year period, 38 (18%) had a bifurcation lesion within the CTO. The most common bifurcation lesions (50%) were on the left anterior descending artery, and the least frequent (21%) on the circumflex coronary artery. CTO recanalization was successful in 35 (92%) patients. The one-stent technique was used in 27 (77%) patients, while the two-stent technique was used in 8 (23%) patients. Conclusion. Bifurcation lesions in the context of PCI CTOs are a relatively common finding in coronary angiography and represent a special challenge for CTO operators. The provisional technique (one-stent technique) is the most common strategy for the treatment of bifurcation lesions in patients with CTO.
Keywords: coronary angiography; coronary occlusion; percutaneous coronary interventions; stents